2017
DOI: 10.4236/psych.2017.810098
|View full text |Cite
|
Sign up to set email alerts
|

High Emotional Arousal Enables Subliminal Detection of Concealed Information

Abstract: The Concealed Information Test (CIT) is an information-detecting technique for criminal investigations. Although it has been shown that emotional arousal plays a specific role in the CIT, the mechanisms by which emotional arousal affects the CIT are unclear. The main purpose of this study was to elucidate the processing pathway for stimuli encoded with emotional arousal in a mock crime before the CIT. In this study, participants viewed emotionally arousing pictures before the mock crime. Participants were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…To clarify the mechanisms involved in emotional arousal in the CIT, the subliminal presentation method is a useful tool to exclude the influence of conscious retrieval. Osugi and Ohira (2017) investigated the effect of emotional arousal at memory encoding using the subliminal presentation method, and reported that the difference scores on P300 amplitude were significantly greater in the High Arousal group than in the Low Arousal group, under both supraliminal and subliminal conditions. This finding supports the notion that P300 is derived from stimulus-driven processing, that is, without a retrieval process, and that emotional arousal may increase the significance of the stimulus at encoding.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the mechanisms involved in emotional arousal in the CIT, the subliminal presentation method is a useful tool to exclude the influence of conscious retrieval. Osugi and Ohira (2017) investigated the effect of emotional arousal at memory encoding using the subliminal presentation method, and reported that the difference scores on P300 amplitude were significantly greater in the High Arousal group than in the Low Arousal group, under both supraliminal and subliminal conditions. This finding supports the notion that P300 is derived from stimulus-driven processing, that is, without a retrieval process, and that emotional arousal may increase the significance of the stimulus at encoding.…”
Section: Discussionmentioning
confidence: 99%